Impacts of nitrogen management on no-till maize production following forage cover crops - Momesso, Letusa [UNESP]; Crusciol, Carlos A.C. [UNESP]; Soratto, Rogério P. [UNESP]; Vyn, Tony J.; Tanaka, Katiuça S. [UNESP]; Costa, Claudio H.M.; Neto, Jayme Ferrari [UNESP]; Cantarella, Heitor (Wiley, 2019)
Crop residue decomposition is slower in no-till (NT) systems, especially in high-biomass systems. Adopting optimum nN management can provide increased soil coverage and synchronize the supply of nutrients with the period of highest crop demand in agroecosystems. A three-year experiment was conducted to assess the feasibility of applying N on forage grass cover crops before termination {Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster [syn. Brachiaria brizantha (Hochst. Ex A. Rich) Stapf] and Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins [syn. B. ruziziensis (R. Germ. and C.M. Evrard)]}, or on forage grass cover crop residues immediately before maize (Zea mays L.) seeding, aiming to supply N to the following maize crop. Urochloa brizantha had 25% higher biomass production and a higher amount of nutrient content than U. ruziziensis. The N application before termination increased biomass production and nutrient content in cover crop residues compared with the conventional fertilization method (30 kg N ha-1 in the maize seeeding plus 170 kg N ha-1 sidedressed in V6 growth stage). Nitrogen applied one day before seeding (DBS) of maize or using conventional method resulted in a higher number of ears per plant and more kernels per ear as well as a higher grain yields of maize (13.8 and 14.1 Mg ha-1, respectively) compared to N applied on cover crops. Our results suggest that, while both forage grass cover crops produced greater amounts of dry matter (DM) and released similar amounts of nutrients, applying all N to cover crops before maize is not a feasible alternative. Nitrogen application 1 DBS could be an alternative management option to supply N to maize because this method resulted in similar nitrogen use efficiency (NUE) as conventional fertilization method.